2017
DOI: 10.4103/aer.aer_35_17
|View full text |Cite
|
Sign up to set email alerts
|

The influence of two different doses of magnesium sulfate on intraocular pressure variations after injection of succinylcholine and endotracheal intubation: A prospective, randomized, parallel three-arm, double-blind, placebo-controlled clinical trial

Abstract: Background:The use of succinylcholine for rapid sequence induction in patients with open globe injuries may be detrimental to the eye.Aim:The aim of this study is to determine if the premedication with magnesium sulfate (MgSO4) could attenuate the increase in intraocular pressure (IOP) associated with succinylcholine injection and intubation.Setting:Operation theaters in a tertiary care University Hospital between December 2014 and July 215.Design:This was a prospective, randomized, parallel three-arm, double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…In the present study, the preventive administration of magnesium sulfate in group B reduced the severity of fasciculation following the injection of succinylcholine. Further, other studies confirmed the findings of the present study regarding the positive and beneficial effects of the prophylactic administration of magnesium sulfate on fasciculation control (26)(27)(28). It seems that magnesium sulfate prevents severe fasciculation reactions by inhibiting acetylcholine secretion after the injection of succinylcholine.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the preventive administration of magnesium sulfate in group B reduced the severity of fasciculation following the injection of succinylcholine. Further, other studies confirmed the findings of the present study regarding the positive and beneficial effects of the prophylactic administration of magnesium sulfate on fasciculation control (26)(27)(28). It seems that magnesium sulfate prevents severe fasciculation reactions by inhibiting acetylcholine secretion after the injection of succinylcholine.…”
Section: Discussionsupporting
confidence: 92%